Role of dalbavancin as combination therapy: evidence from the literature and clinical scenarios. Issue 7 (3rd July 2022) - Cacopardo, Bruno; Cattaneo, Dario; Cortese, Francesco; Di Luca, Mariagrazia; Falcone, Marco; Marchetti, Giulia; Tascini, Carlo; Tiseo, Giusy; Venditti, Mario
ABSTRACT: Introduction: The off-label use of dalbavancin in patients with infections other than acute bacterial skin and skin structure infections (ABSSSI) represents an interesting therapeutic option. Its use as monotherapy or in combination with other antibiotics should be better defined. Areas covered: The aim of this review is to summarize evidence about the potential role of dalbavancin in combination with other antibiotics and describe clinical scenarios in which combination regimens including dalbavancin are useful. The studies were retrieved from PubMed using different combinations of keywords ('dalbavancin, ' 'combination, ' and 'synergy'). Expert opinion: Limited data about the use of dalbavancin in monotherapy or combined with other antibiotics are available. In vitro assays showed a synergistic effect of dalbavancin when combined with beta-lactam antibiotics. The use of dalbavancin as a combination therapy in patients with ABSSSI did not demonstrate superiority compared to monotherapy. Conversely, combination regimens including dalbavancin may be useful in specific infection types, such as bone and prosthetic joint infections or subacute/chronic intravascular infections with no possibility of device removal. Potential partner drugs might be rifampin, beta-lactams, fluoroquinolones, doxycycline, and trimethoprim/sulfamethoxazole. The choice of the companion drug should be tailored on in vitro results of synergistic tests, patient's profile, and type of infection.